Improving Student Learning Outcomes in Cultural Arts Learning (Dance) With a Direct Learning Model (Direct Instruction) - Junita Wulandari, Zona; Susmiarti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to improve the learning outcomes of grade VII students by using the Direct Instruction Learning Model in Cultural Arts (dance) Subjects at SMP Angkasa Lanud Padang. This type of research is Classroom Action Research (PTK) using 2 cycles. The tools used in this study were stationery and cameras using observation sheets as data collection. Data collection techniques are carried out by observation, interviews, documentation and tests. The data is analyzed using a percentage formula. The learning outcomes of grade VII students of SMP Angkasa Lanud Padang improved well. It can be seen from the results of the students' theory written test in cycle 1 with an average score of 78.80%, and in cycle 2 with an average score of 83.83%. In cycle 1 psychometric test results with an average score of 78.70% and in cycle 2 with an average score of 83.12%. Student learning activities in cycle 1 with an average score of 58.33% and in cycle 2 student learning activities have reached the target desired by researchers with an average of 73.40. Overall, from cycle 1 and cycle 2, assessment of student learning activities based on a recapitulation of good assessments.